2011
DOI: 10.1007/s10570-011-9622-z
|View full text |Cite
|
Sign up to set email alerts
|

First report on the kinetics of the uncatalyzed esterification of cellulose under homogeneous reaction conditions: a rationale for the effect of carboxylic acid anhydride chain-length on the degree of biopolymer substitution

Abstract: The kinetics of the homogeneous acylation of microcrystalline cellulose, MCC, with carboxylic acid anhydrides with different acyl chain-length (Nc; ethanoic to hexanoic) in LiCl/N,N-dimethylacetamide have been studied by conductivity measurements from 65 to 85°C. We have employed cyclohexylmethanol, CHM, and trans-1,2-cyclohexanediol, CHD, as model compounds for the hydroxyl groups of the anhydroglucose unit of cellulose. The ratios of rate constants of acylation of primary (CHM; Prim-OH) and secondary (CHD; S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…The dependence of DS on the anhydride employed is similar to that observed elsewhere, i.e., ethanoic ≈ hexanoic > butanoic 19, 55. As recently shown, this dependence of DS on the length of the acyl moiety of the anhydride is due to subtle changes in‐ and compensations of the enthalpy and entropy of activation 56…”
Section: Resultssupporting
confidence: 85%
“…The dependence of DS on the anhydride employed is similar to that observed elsewhere, i.e., ethanoic ≈ hexanoic > butanoic 19, 55. As recently shown, this dependence of DS on the length of the acyl moiety of the anhydride is due to subtle changes in‐ and compensations of the enthalpy and entropy of activation 56…”
Section: Resultssupporting
confidence: 85%
“…The reason for this result was that the higher steric hindrance of the two bulky substituents, BrBiB and CPAC, caused them to be unable to reach the secondary OH groups of cellulose, which had more steric hindrance. This result agreed with those of Nawaz et al (2012), who found that the preference for the C6 position increased as a function of increasing molecular volume of the reagent.…”
Section: Difference In Reactivity Among the Three Oh Groupssupporting
confidence: 92%
“…The low reactivity of cellulose with vinyl esters with long aliphatic chains is due to their stronger steric hindrance effect (Cao et al 2014). Nawaz et al (2012) concluded that the DS values of the cellulose esters depended on the carbon atoms of the acyl group of the derivatizing agent because of a complex dependence of the activation enthalpy and entropy terms on the structural variable. Moreover, according to Dicke (2004), the formation of regioselective derivatives only succeeds by reaction with bulky groups, which primarily react with sterically favored hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because these methods merely indicate the formation/disappearance of ions, an independent proof should be given, for example, by isolation of the reaction product under the conditions of the kinetic run. This approach was followed in acylation of cellulose in LiCl/N,N-dimethylacetamide where the cellulose esters formed were isolated at the end of the kinetic experiments [130].…”
Section: Measurement Of Conductancementioning
confidence: 99%